Evaluation of environmental impacts related to the implementation of the business district of Morro Agudo/SP: Possible scenarios and mitigation strategies - Duarte, João Paulo Pereira; Farias, Cátia Araújo; Hanai, Frederico Yuri (National Journal of City Management, 2024)
For decades, debates and discussions about the environment and its preservation have gained strength internationally, especially on the issue of climate change associated with greenhouse gases-GHG. For this reason, normative initiatives have been adopted to minimize or redirect anthropic practices that can contribute to the preservation of nature, in order to keep natural resources available, and with quality, for future generations. In this scenario, this work evaluated the environmental impacts related to the implementation of the Business District of Morro Agudo/SP, presenting possible scenarios and strategies to mitigate the anthropic activity. After the studies, it was concluded that, for the implementation of the business district of the municipality, there would be positive and negative impacts for the place and its citizens. Despite the interventions in the natural resources of the delimited area, the pre-established compensation is consistent with the mitigation of impacts, as well as the strategies strengthen the conservation and recovery of the municipality's resources.
Keywords: Environment; Public Policy; AIA